2018
DOI: 10.1166/jnn.2018.15718
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic NiFe2O4/Exfoliated Graphite as an Efficient Sorbent for Oils and Organic Pollutants

Abstract: This study aimed to fabricate, characterize and investigate the applicability of nickel ferrite (NiFe2O4 decorated exfoliated graphite for adsorptive removal of oils and organic compounds. The exfoliated graphite/NiFe2O4 was synthesized via a simple two-step process: (i) exfoliation of the lowcost natural graphite flakes using H2O2 as oxidizing agent and H2SO4 as intercalating agent, (ii) decoration of magnetic NiFe2O4 using the acid citric-based sol-gel process. The synthesized exfoliated graphite/NiFe2O4 hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Furthermore, the sorption amount of EG-MnFe 2 O 4 for crude oil (33.07 g/g) is higher than for diesel oil (32.20 g/g). The reason may be due to the larger glutinosity of crude oil, resulting in the higher density of oil molecules occupied inside pores [15]. Comparably, the adsorption amount of bare EG for CO and DO was found to be 47.7 g/g and 39.8 g/g within 4 minutes, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the sorption amount of EG-MnFe 2 O 4 for crude oil (33.07 g/g) is higher than for diesel oil (32.20 g/g). The reason may be due to the larger glutinosity of crude oil, resulting in the higher density of oil molecules occupied inside pores [15]. Comparably, the adsorption amount of bare EG for CO and DO was found to be 47.7 g/g and 39.8 g/g within 4 minutes, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption capacity of EG-CoFe 2 O 4 was found to be 48.93 g/g, 42.75 g/g, and 33.18 g/g, respectively, for engine oil, crude oil, and diesel oil. The study by Vinh et al (2018) on the composites of EG and NiFe 2 O 4 showed the magnetism value and surface area of 14.2 emu/g and 32.9 m 2 /g, respectively, with high sorption capacity for diesel oil at 32.56 g/g [15]. The latter investigations improved the saturation magnetization of EG by introducing the CoFe 2 O 4 and NiFe 2 O 4 up to 42 emu/g and 19 emu/g, respectively [13].…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods, because of economy and efficiency, the adsorption method at the solid/liquid interface has been broadly applied [10,11]. Adsorption method is an effective means of dyeing wastewater treatment, because of its convenient operation, simplicity of design, low cost, insensitive to toxic substances and good treatment effect have attracted much attention [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…19 Differnent nanomaterials and numerous approaches that report on its chemical design exhibit varying features and performances. [57][58][59] There are several uses for the NiFe 2 O 4 particles, such as sensors, 60 energy storage, 61 synthesis, 62 absorbent, 63 photocatalytic degradation, 64-66 electrocatalysis, 67 energy production, 68 drug delivery systems. [69][70][71] Mixed ferrites of metals with a spinel structure are the same inorganic compounds.…”
mentioning
confidence: 99%